Application of 1-hydroxyethylidene-1, 1-diphosphonic acid in boiler water for industrial boilers - Zeng, Bin (Water science and technology : a journal of the International Association on Water Pollution Research, 2013)
The primary method used for boiler water treatment is the addition of chemicals to industrial boilers to prevent corrosion and scaling. The static scale inhibition method was used to evaluate the scale inhibition performance of 1-hydroxyethylidene-1, 1-diphosphonic acid (HEDP). Autoclave static experiments were used to study the corrosion inhibition properties of the main material for industrial boilers (20# carbon steel) with an HEDP additive in the industrial boiler water medium. The electrochemical behavior of HEDP on carbon steel corrosion control was investigated using electrochemical impedance spectroscopy and Tafel polarization techniques. Experimental results indicate that HEDP can have a good scale inhibition effect when added at a quantity of 5 to 7 mg/L at a test temperature of not more than 100 °C. To achieve a high scale inhibition rate, the HEDP dosage must be increased when the test temperature exceeds 100 °C. Electrochemical and autoclave static experimental results suggest that HEDP has a good corrosion inhibition effect on 20# carbon steel at a concentration of 25 mg/L. HEDP is an excellent water treatment agent